2020
DOI: 10.1097/jom.0000000000001846
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Risk Factor Changes Over 5 Years Among Male and Female US Firefighters

Abstract: Objective: To examine changes in measures of cardiovascular health in male and female firefighters over 5 years. Methods: Anthropometrics and biomarkers of cardiovascular health from two occupational medical exams separated by 5 years (2009 to 2016) were examined from a cohort of US career firefighters in Virginia (males, n = 603; females, n = 69). Changes over time were tested using paired t-tests and McNemar's tests. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
56
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 17 publications
14
56
0
1
Order By: Relevance
“…Hypertension prevalence has been shown to increase with age in the general population [27], and in 2002, using the hypertension cut-off values of that time (≥140/90 mmHg), Davis and colleagues reported a hypertension prevalence of 12.0% among young firefighters and 31.6% in older firefighters [24]. While not formally tested in our study, female firefighters had lower blood pressure values than male firefighters on average, which is consistent with previous findings [22,23]. The results of this study, however, extend previous research by showing that female firefighters' blood pressure reached values more similar to male firefighters at older ages.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hypertension prevalence has been shown to increase with age in the general population [27], and in 2002, using the hypertension cut-off values of that time (≥140/90 mmHg), Davis and colleagues reported a hypertension prevalence of 12.0% among young firefighters and 31.6% in older firefighters [24]. While not formally tested in our study, female firefighters had lower blood pressure values than male firefighters on average, which is consistent with previous findings [22,23]. The results of this study, however, extend previous research by showing that female firefighters' blood pressure reached values more similar to male firefighters at older ages.…”
Section: Discussionsupporting
confidence: 90%
“…To date, studies on hypertension and other CVD risk factors in firefighters have generally reported on small sample sizes, limited geographical regions, a select group of firefighters, and mainly males [17][18][19][20][21][22][23]. Currently, only one study has investigated blood pressure and hypertension across different age groups of firefighters [24], and studies that have compared hypertension in the fire service to the general population have found mixed results and were based on small samples [17,19,20,24].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is highly prevalent among US firefighters (24–35%) [ 1 5 ] and is associated with impaired work performance [ 6 ], increased risk of injury [ 7 , 8 ] and duty-related sudden cardiac events [ 9 ]. Sudden cardiac events are the leading cause of duty-related deaths in the fire service [ 10 ], and coronary heart disease and structural heart changes (cardiomegaly and LVH) have been identified in over 80% of cardiac cases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several longitudinal studies have shown that, on average, firefighters gain weight as they age (~ 0.5 kg/yr) [ 5 , 18 , 19 ] and that firefighters who gained weight over a 5-year period had adverse changes in cardiovascular health [ 20 ]. Previous studies, reporting on data from the 1980s and 1990s, suggests that while both age groups gain weight over time, younger firefighters gain more weight each year than older firefighters [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of low fitness, obesity, and cardiovascular disease (CVD) risk factors, such as hypercholesterolemia, hypertension, and high blood glucose, among United States (US) career firefighters is high [ 1 ]. When these risk factors interact with the strenuous physical activity, emotional stress, and environmental pollutants characteristic of the firefighter profession, the risk of CVD events is increased [ 2 ].…”
Section: Introductionmentioning
confidence: 99%